Diagnostic Accuracy of Tc99m-Sestamibi in Differentiating Benign vs Malignant Renal Masses - Sikandar, Zeeshan; Hussain, Fida; Dar, Zaigham Salim; Sharoon, Rebecca; Tariq, Aleena; Ibrahim, Muhammad Usman (Pakistan Armed Forces Medical Journal, 2025)
Objective: To assess the role of pre-operative Tc-99m sestamibi scintigraphy in Differentiating Benign vs Malignant Renal Masses. Study Design: Cross-sectional study Place and Duration of Study: Nuclear Medical Centre, Armed Forces Institute of Pathology, Rawalpindi Pakistan, from Jun 2022 to Jun 2023. Methodology: A total of 41 patients with T1 solid renal tumours who were eligible for undergoing surgery or suitable for biopsy underwent Tc-99m sestamibi scintigraphy during study duration. Tc-99m sestamibi scintigraphy findings were correlated with post-operative histopathology results to determine accuracy of scintigraphic study. Results: Out of forty-one patients, 24(58.5%) were men and 17(41.5%) were women with a mean age 54.39±13.28 years. Among total patients, 24(58.5%) had clear cell RCC, 5(12.2%) had papillary RCC, 3(7.3%) had chromophobe RCC, 2(4.9%) had oncocytic papillary RCC, 5(12.2%) had oncocytoma and 2(4.9%) had lipid poor angiomyolipoma variant on histopathology. Overall, 7(17.07%) patients had benign pathology. Tc-99m Sestamibi SPECT/CT correctly identified all benign lesions (oncocytoma and lipid poor angiomyolipoma) and two variants of malignant pathology (chromophobe and oncocytic papillary RCC) yielding a sensitivity of 100% while specificity of 85.29% in detecting benign lesions. There was significant correlation between positive Tc-99m sestamibi findings and benign pathology with a p-value <0.001. Conclusions: Tc-99m sestamibi scintigraphy plays a significant role in pre-operative evaluation of renal masses and offers a non-invasive modality to help differentiate benign and malignant renal masses.